Current status of mechanical circulatory support for treatment of advanced end-stage heart failure: successes, shortcomings and needs. (4th May 2017) - Sunagawa, Gengo; Koprivanac, Marijan; Karimov, Jamshid H.; Moazami, Nader; Fukamachi, Kiyotaka
ABSTRACT: Introduction : Heart failure (HF) remains a major global burden in terms of morbidity and mortality. Despite advances in pharmacological and resynchronization device therapy, many patients worsen to end-stage HF. Although the gold-standard treatment for such patients is heart transplantation, there will always be a shortage of donor hearts. Areas covered : A left ventricular assist device (LVAD) is a valuable option for these patients as a bridge measure (to recovery, to candidacy for transplant, or to transplant itself) or as destination therapy. This review describes the current indications for and complications of the most commonly implanted LVADs. In addition, we review the potential and promising new LVADs, including the HeartMate 3, MVAD, and other LVADs. Studies investigating each were identified through a combination of online database and direct extraction of studies cited in previously identified articles. Expert commentary : The goal of LVADs has been to fill the gap between patients with end-stage HF who would likely not benefit from heart transplantation and those who could benefit from a donor heart. As of now, the use of LVADs has been limited to patients with end-stage HF, but next-generation LVAD therapy may improve both survival and quality of life in less sick patients.